Platelet-Binding of the von Willebrand Factor - Green, David; Muller, Hendrik P (Thrombosis and Haemostasis, 1978)
The aggregation of platelets by the antibiotic, ristocetin, requires a plasma cofactor (VIII:vWF) and one or more specific binding sites on the platelet membrane. The interaction between VIII:vWF and the platelet was examined using VIII:vWF labelled with 125 I. In the presence of ristocetin (1.5 mg/ml), from 70 to 90% of the 125 I-VIII:vWF became platelet- bound. By contrast, only 21% was bound with thrombin (2.5 u/ml), and 2.2% with buffer alone. Fractionation of the platelets revealed that peak radioactivity was present in the membrane fraction. Treatment of ristocetin-reacted platelets with either chymotrypsin, 100 ug/ml, or trypsin, 75 ug/ml, resulted in the partial release of the membrane-bound radioactivity. It is concluded that VIII:vWF binds to the platelet membrane in the presence of ristocetin.